1991
DOI: 10.3168/jds.s0022-0302(91)78242-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moisture in Total Mixed Rations on Feed Consumption and Milk Production and Composition in Holstein Cows

Abstract: The DM levels in total mixed rations were maintained at 62.7, 52.8, and 45.8% by incorporating 38% of the DM from alfalfa silages of twi different DM contents into the ration to determine the effect on milk production and composition when fed to lactating Holstein cows. The alfalfa silages were stored at approximately 25 and 50% DM and harvested from the same field on consecutive days either direct-cut and bagged or wilted overnight before bagging. Silages were used (minimum of 8.5 kg of Dm/d) in a total mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 5 publications
0
11
0
2
Order By: Relevance
“…the TMR for adult cows has been inconclusive; some studies describe increases in DMI (Lahr et al, 1983) and others report negative effects (Kellems et al, 1991). Sorting activity was not affected by moisture content of the TMR (Table 4).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…the TMR for adult cows has been inconclusive; some studies describe increases in DMI (Lahr et al, 1983) and others report negative effects (Kellems et al, 1991). Sorting activity was not affected by moisture content of the TMR (Table 4).…”
Section: Resultsmentioning
confidence: 97%
“…Previous work on adult † E-mail: marina.vonkeyserlingk@ubc.ca animal 1722 dairy cattle and older heifers has shown increased consumption (Lahr et al, 1983), reduced sorting (Leonardi and Armentano, 2003;Leonardi et al, 2005), less dust (ArzolaÁlvarez et al, 2010) and lower feed losses due to wind when the moisture content was increased by adding water, but other studies have reported either no effect (Fish and DeVries, 2012), or decreased feed intake (Kellems et al, 1991;Felton and DeVries, 2010) and increased sorting (Miller-Cushon and DeVries, 2009;Felton and DeVries, 2010) with greater dietary moisture. Furthermore, wetter rations are prone to spoilage especially at higher environmental temperatures (Felton and DeVries, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These small, but positive, effects of straw inclusion on total DM intake may be driven by a number of factors. For example, straw inclusion increased the DM content of the forage mixture offered, and this may have improved the intake characteristics of the ration ( Lahr et al ., 1983 ; Kellems et al ., 1990 ). It is also possible that straw inclusion stimulated chewing activity and saliva production, during both ingestion and rumination, with an associated increase in rumen pH, resulting in a more stable rumen environment.…”
Section: Discussionmentioning
confidence: 99%
“…; Kellems et al . ). Moreover, the advantages of feeding TMR to cattle have been widely accepted in the dairy industry in developed countries.…”
Section: Introductionmentioning
confidence: 97%